2013
DOI: 10.1287/mnsc.2013.1713
|View full text |Cite
|
Sign up to set email alerts
|

“Nursevendor Problem”: Personnel Staffing in the Presence of Endogenous Absenteeism

Abstract: The problem of determining nurse staffing levels in a hospital environment is a complex task due to variable patient census levels and uncertain service capacity caused by nurse absenteeism. In this paper we combine an empirical investigation of the factors affecting nurse absenteeism rates with an analytical treatment of nurse staffing decisions using a novel variant of the newsvendor model. Using data from the emergency department of a large urban hospital, we find that absenteeism rates are consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 47 publications
(40 reference statements)
1
49
1
1
Order By: Relevance
“…Using multiple settings within healthcare KC and Terwiesch (2009) show that service rates are endogenous to load. Multiple papers have built upon this finding: to replicate it in other contexts (Staats and Gino 2012), to show that quality may suffer due to load (Kuntz, Mennicken and Scholtes 2015), to show that workers may burn out due to load (Green, Savva and Savin 2012) and more generally show how load can alter behavior in an operating system (Tan and Netessine 2014;Berry Jaeker and Tucker 2015;Kim et al 2015). A key assumption in this line of work is that as individuals experience more load, they choose to work faster in the short-term, although this speeding up may negatively impact performance in the long-term.…”
Section: Introductionmentioning
confidence: 95%
“…Using multiple settings within healthcare KC and Terwiesch (2009) show that service rates are endogenous to load. Multiple papers have built upon this finding: to replicate it in other contexts (Staats and Gino 2012), to show that quality may suffer due to load (Kuntz, Mennicken and Scholtes 2015), to show that workers may burn out due to load (Green, Savva and Savin 2012) and more generally show how load can alter behavior in an operating system (Tan and Netessine 2014;Berry Jaeker and Tucker 2015;Kim et al 2015). A key assumption in this line of work is that as individuals experience more load, they choose to work faster in the short-term, although this speeding up may negatively impact performance in the long-term.…”
Section: Introductionmentioning
confidence: 95%
“…Huckman and Staats (2011) answer this question in the context of fluid teams (i.e., teams that are formed and dissembled quickly) in the software services industry. Green et al (2013) examine how the workload of the team affects the participation of team members. Although the endogeneity issue is likely to be absent given the specific contexts of their studies, future research should account for the fact that workers self-select into teams and that there are potentially unobserved factors that guide how managers construct teams.…”
Section: Services Management and Retailing (Onlinementioning
confidence: 99%
“…Research on the role of scheduling on task performance has investigated the optimal allocation of labor to tasks over time and has addressed problems such as machine inspection scheduling (Lee and Rosenblatt 1987) and workforce scheduling (Green, Savin, and Savva 2013). Studies of task sequencing have shown, for example, that scheduling similar tasks consecutively can improve performance by increasing task repetition and reducing delays incurred from switching tasks (e.g., Gino 2012, Ibanez et al 2016).…”
Section: The Drivers Of Task Performancementioning
confidence: 99%